Evaluation of the effect of a new sugarcane-derived cystatin (CaneCPI-5) on the profile and viability of microcosm biofilm, as well as on the prevention of dentin demineralization - Câmara, João Victor Frazão (2021)
Recently, a new sugarcane-derived cystatin (CaneCPI-5) was produced in a heterologous expression system and demonstrated a high binding capacity to enamel, protecting against enamel erosion in vitro. In addition, matrix proteases are very important for the progression of caries in dentin and cystatins, including CaneCPI-5, are inhibitors of cysteine-catepsins, which may have an additional effect in preventing caries in dentin. The objective of this work was to evaluate the effect of different concentrations of CaneCPI-5 on the bacterial profile and viability of a microcosm biofilm, as well as on the prevention of dentin demineralization. To form the microcosm biofilm, saliva from 10 healthy individuals was collected, diluted (70% saliva and 30% glycerol) and mixed with McBain\'s artificial saliva (1:50) to form the cariogenic biofilm. Samples (4 mm x 4 mm) of bovine dentin (n=90) were prepared for microcosm biofilm formation for 5 days, treated daily (1x60s/day) with concentrations of CaneCPI-5 0.025 and 0.05 mg/ml, 0.12% chlorhexidine (CHX) (positive control), Fluoride (500 ppm F, as NaF) or PBS (negative control). Evaluation of the profile of the formed biofilm (colony forming units) and the metabolic activity of the biofilm through the addition of resazurin were carried out. The demineralization caused by the biofilm under the conditions studied was measured by transversal microradiography. CXH reduced the metabolic activity of the microcosm biofilm compared to the negative control and treated groups (p 0.01). CHX and F significantly reduced the counts of total microorganisms, mutans streptococci and lactobacilli when compared to the negative control. None of the treatments were able to significantly reduce dentin demineralization compared to the negative control. In the evaluated model, CaneCPI-5 neither changed the profile and viability of the microcosm biofilm nor protected the dentin against demineralization.